2014
DOI: 10.3390/ijerph111213117
|View full text |Cite
|
Sign up to set email alerts
|

Chlorpyrifos Exposure and Respiratory Health among Adolescent Agricultural Workers

Abstract: Chlorpyrifos (CPF) is a commonly used organophosphate insecticide (OP). In adults, exposure to OPs has been inconsistently associated with reduced lung function. OP exposure and lung function has not been assessed in adolescents. The objective of this study was to assess CPF exposure and lung function among Egyptian adolescents. We conducted a 10-month study of male adolescent pesticide applicators (n = 38) and non-applicators of similar age (n = 24). Urinary 3,5,6-trichloro-2-pyridinol (TPCy), a CPF-specific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 35 publications
0
23
0
Order By: Relevance
“…Participants were recruited from two districts (Al-Shohada and Berket El-Sabea’) in the Menoufia Governorate, Egypt (Callahan et al 2014; Crane et al 2013; Khan et al 2014; Rohlman et al 2016). All pesticide applicators between 12 and 21 years of age from both districts were invited to participate in the study and 100% accepted.…”
Section: Methodsmentioning
confidence: 99%
“…Participants were recruited from two districts (Al-Shohada and Berket El-Sabea’) in the Menoufia Governorate, Egypt (Callahan et al 2014; Crane et al 2013; Khan et al 2014; Rohlman et al 2016). All pesticide applicators between 12 and 21 years of age from both districts were invited to participate in the study and 100% accepted.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have reported an association between pesticides and various health effects, including adverse respiratory health outcomes such as asthma, rhinitis, and non-specific respiratory symptoms [1,2,3,4,5]. Various agents have been associated with these adverse respiratory health effects.…”
Section: Introductionmentioning
confidence: 99%
“…, , ; Callahan et al. ) during seasonal applications were found. Similarly, adolescent Egyptian pesticide applicators have also been shown to have limit PPE use and correspondingly high concentrations of TCPy (Crane et al.…”
Section: Pesticide Use In Developing Countriesmentioning
confidence: 93%
“…Consequently, appropriate handling and use of PPE during pesticide applications are not adhered to widely. For instance, among adult Egyptian pesticide applicators with documented limited use of PPE extremely high urinary concentrations of the chlorpyrifos-specific metabolite 3,5,6-trichloro-2-pyridinol (TCPy) (Farahat et al 2003(Farahat et al , 2010(Farahat et al , 2011Callahan et al 2014) during seasonal applications were found. Similarly, adolescent Egyptian pesticide applicators have also been shown to have limit PPE use and correspondingly high concentrations of TCPy (Crane et al 2013).…”
Section: Pesticide Use In Developing Countriesmentioning
confidence: 99%